2007
DOI: 10.1073/pnas.0708899104
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thymic selection of FoxP3 + regulatory T cells in the NOD mouse model of autoimmune diabetes

Abstract: FoxP3 ؉ CD4 ؉ regulatory T cells (Tregs) play a key role in the maintenance of peripheral self-tolerance, and it has been suggested that diabetes-susceptible nonobese diabetic (NOD) mice are defective in the generation and numbers of Tregs. We found thymic selection of Tregs to be under genetic control. Fetal thymic organ cultures on the NOD background required 3-to 10-fold more antigen than corresponding cultures on the B6 background for optimal induction of Tregs, but once the threshold for induction was rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
71
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 48 publications
12
71
2
Order By: Relevance
“…Trd1 fully explains the difference between NOD and B6 or B10 mice. The discrepancy between both studies may be explained by the phenotype analyzed, generation of Treg cells through fetal organ culture in the paper by Feuerer et al [11], and underscores the complexity of the trait studied.Trd1 does not contain the genes encoding antigen-presenting MHC class (I and) II molecules that are located telomeric to the Trd1 region. It therefore appears that these molecules are not involved in the quantitative difference of Foxp3 + CD4SP Treg-cell development in NOD vs. B6 mice.…”
mentioning
confidence: 86%
See 3 more Smart Citations
“…Trd1 fully explains the difference between NOD and B6 or B10 mice. The discrepancy between both studies may be explained by the phenotype analyzed, generation of Treg cells through fetal organ culture in the paper by Feuerer et al [11], and underscores the complexity of the trait studied.Trd1 does not contain the genes encoding antigen-presenting MHC class (I and) II molecules that are located telomeric to the Trd1 region. It therefore appears that these molecules are not involved in the quantitative difference of Foxp3 + CD4SP Treg-cell development in NOD vs. B6 mice.…”
mentioning
confidence: 86%
“…Natural Treg cells are generated in the thymus where the processes of positive and negative selection shape their autospecific TCR repertoire [10]. Two groups have shown quantitative differences in Treg-cell development in NOD mice [11,12]. Feuerer et al [11] reported increased levels of Treg cells in NOD vs. B6.H-2 g7 thymi.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that nTregs do not have to be the exclusive protective factor against autoimmune disease was previously demonstrated in autoimmunity-prone NOD mice, which surprisingly generate nTregs more effectively than do healthy mice (61).…”
Section: Discussionmentioning
confidence: 99%